Anode piece, electrochemical device and electronic device including said anode piece

The negative electrode piece with a layered structure of silicon-based and graphite particles, featuring reduced Si content in the surface region of silicon-based particles, addresses the cycling and expansion challenges in lithium-ion batteries by reducing surface stress and improving interface stability.

JP7659068B2Active Publication Date: 2025-04-08NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023538978
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-28
Publication Date
2025-04-08
Estimated Expiration
2040-12-28

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries face challenges with the cycling characteristics and expansion/deformation issues due to the high volume change rate of silicon-based materials during lithium desorption, leading to stress concentration and interface instability.

Method used

A negative electrode piece is developed with a negative electrode material layer comprising silicon-based particles and graphite particles, where silicon-based particles with a particle diameter over 3 μm have a lower Si content in the surface region compared to the internal region, reducing surface stress and improving interface stability.

Benefits of technology

This configuration effectively enhances the cycle characteristics and reduces expansion/deformation issues in lithium-ion batteries, maintaining high gram capacity while minimizing contact with the electrolyte and formation of the solid electrolyte interface film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659068000013
    Figure 0007659068000013
  • Figure 0007659068000014
    Figure 0007659068000014
  • Figure 0007659068000015
    Figure 0007659068000015
Patent Text Reader

Abstract

The present invention provides a negative electrode piece, an electrochemical device including the negative electrode piece, and an electronic device, in which the negative electrode material layer of the negative electrode piece includes silicon-based particles and graphite particles, and in the silicon-based particles having a particle diameter of more than 3 μm, the Si content in the surface region is smaller than the Si content in the internal region. This reduces the surface stress of the negative electrode piece, thereby improving the interfacial stability between the silicon-based particles and the electrolyte, and effectively improving the cycle characteristics and expansion and deformation problems of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the electrochemical field, and in particular to anode strips, electrochemical devices and electronic devices including the anode strips. [Background technology]

[0002] Lithium ion secondary batteries have advantages such as high energy storage density, high open circuit voltage, low self-discharge rate, long cycle life, and excellent safety, and are widely used in various fields such as electric energy storage, mobile electronic devices, electric vehicles, and aerospace equipment. With the rapid development of mobile electronic devices and electric vehicles, the market has increasingly higher requirements for the energy density, safety, cycle characteristics, and service life of lithium ion secondary batteries.

[0003] Silicon-based materials have a theoretical capacity of 4200mAh / g, making them the negative electrode material with the highest theoretical capacity known to date, and silicon is abundant and inexpensive, so currently, lithium-ion secondary battery negative electrode pieces often use silicon-based materials as next-generation negative electrode materials with high gram capacity. However, silicon-based materials have a high volume change rate of over 300% during the lithium desorption process, which is prone to causing stress concentration on the surface of silicon-based materials, affecting the interface stability between silicon-based particles and electrolyte, and resulting in a decline in the cycle characteristics of lithium-ion secondary batteries. Summary of the Invention

[0004] The present invention provides a negative electrode piece, an electrochemical device and an electronic device including the negative electrode piece, and aims to improve the cycle characteristics and the expansion deformation problem of the electrochemical device.

[0005] In the following, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to only a lithium ion battery.

[0006] The specific technical proposals are as follows: A first aspect of the present invention provides an anode piece comprising an anode material layer, the anode material layer comprising silicon-based particles and graphite particles, the silicon-based particles comprising silicon and carbon, and in the silicon-based particles having a particle size of more than 3 μm, a Si content in a surface region is less than a Si content in an inner region.

[0007] In one embodiment of the present invention, the negative electrode material layer includes silicon-based particles and graphite particles, and the silicon-based particles may include silicon and carbon, and the silicon-based particles may further include oxygen, nitrogen, phosphorus, sulfur, etc. In the present invention, the type of silicon-based particles is not particularly limited as long as the object of the present invention can be achieved, and may include at least one of nanosilicon, silicon-nanosilicon, silicon-carbon, nanosilica, and silicon-metal alloy, etc. By including silicon-based particles and graphite particles in the negative electrode material layer, it is possible to reduce contact with the electrolyte and reduce the generation of a solid electrolyte interface film (SEI) while maintaining a high gram capacity of the negative electrode material layer.

[0008] In the present invention, the "surface region" refers to a part of the shell of the silicon-based particle that is close to the outer surface of the silicon-based particle and extends from the outer surface of the silicon-based particle toward the center, and the "internal region" refers to a part of the spherical region of the silicon-based particle that is away from the outer surface of the silicon-based particle and extends from the outer surface of the silicon-based particle toward the center. The size of each of the above regions can be selected by those skilled in the art according to actual needs.

[0009] In the present invention, for silicon-based particles having a particle diameter of more than 3 μm, the Si content in the surface region is smaller than the Si content in the inner region, so that the expansion deformation is reduced, and the stress concentration on the surface caused by the expansion of silicon due to lithium absorption can be effectively reduced, and the interface stability between the silicon-based particles and the electrolyte can be improved. Note that, for silicon-based particles having a particle diameter of less than 3 μm, the distribution of the Si content is not particularly limited as long as the object of the present invention can be achieved.

[0010] In general, the anode piece provided in the present invention includes an anode material layer, which includes silicon-based particles and graphite particles, and for silicon-based particles with a particle diameter of more than 3 μm, the Si content in the surface region is smaller than the Si content in the inner region, thereby reducing the stress concentration on the surface caused by the expansion of silicon in the anode piece due to lithium absorption, improving the interfacial stability between the silicon-based particles and the electrolyte, and effectively improving the cycle characteristics and the problems of expansion and deformation of lithium ion batteries.

[0011] In one embodiment of the present invention, when the mass percentage of Si in the surface region from the outer surface of the silicon-based particle to the outer surface is less than 0.2 μm, and the mass percentage of Si in the inner region from the outer surface of the silicon-based particle to the outer surface is more than 0.2 μm, M1 and M2 satisfy M2>M1. If the surface region is too small, the stress caused by expansion cannot be effectively released, so that cracks are likely to occur on the surface of the silicon-based particle during cycling, and the electrolyte corrodes the inside of the silicon-based particle along the cracks, causing the collapse of the silicon-based particle structure, and at the same time, consuming lithium ions in the lithium-ion battery and accelerating the decay of capacity. If the surface region is too large, the silicon content of the entire silicon-based particle is low, and the gram capacity is accordingly reduced, and the energy density of the lithium-ion battery is reduced. By controlling the surface region to the region from the outer surface of the silicon-based particle to the outer surface of the silicon-based particle to the outer surface of the silicon-based particle to the outer surface of the silicon-based particle, the stress concentration on the surface caused by the expansion of the negative electrode piece can be effectively improved, and the cycle characteristics and expansion deformation problems of the lithium-ion battery can be improved.

[0012] In the present invention, the "distance" in the above "distance from the outer surface of the silicon-based particle to the outer surface" and "distance to the outer surface of the silicon-based particle" refers to the maximum distance perpendicular to the tangent line from the surface region to the outer surface. In the above embodiment, the "distance" is 0.2 μm. In the present invention, the "distance" is not particularly limited as long as the object of the present invention can be achieved, and can be selected, for example, from 0.04 μm, 0.08 μm, or 0.15 μm.

[0013] In one embodiment of the present invention, the sum α of the porosity α1 of the silicon-based particles and the porosity α2 of the negative electrode piece satisfies 40%<α<90%. For example, the lower limit of the sum α of the porosity α1 of the silicon-based particles and the porosity α2 of the negative electrode piece may include 42%, 45%, 46%, 48%, 55%, 57%, or 60%, and the upper limit of the sum α of the porosity α1 of the silicon-based particles and the porosity α2 of the negative electrode piece may include 65%, 68%, 72%, 77%, 86%, or 87%. By controlling the sum α of the porosity α2 of the negative electrode piece and the porosity α1 of the silicon-based particles to the above range, the cycle characteristics and expansion prevention characteristics of the lithium-ion battery are significantly improved.

[0014] In the present invention, the "porosity α1 of the silicon-based particles" refers to the volume percentage of the pores in the silicon-based particles relative to the total volume of the silicon-based particles. In the present invention, the "porosity α2 of the negative electrode pieces" refers to the volume percentage of the pores between each particle of the negative electrode pieces relative to the total volume of the negative electrode pieces.

[0015] In the present invention, the pores of the silicon-based particles and the negative electrode pieces each independently include micropores having a pore size of less than 2 nm, mesopores having a pore size of 2 nm to 50 nm, or macropores having a pore size of more than 50 nm. In the present invention, the number of the above-mentioned micropores, mesopores, and macropores is not particularly limited as long as the object of the present invention can be achieved.

[0016] In one embodiment of the present invention, the porosity α1 of the silicon-based particles is 15% to 60%, and for example, the lower limit of the porosity α1 of the silicon-based particles may include 15%, 16%, 18%, 25%, 30%, or 33%, and the upper limit of the porosity α1 of the silicon-based particles may include 38%, 45%, 47%, 56%, or 60%. If the porosity α1 of the silicon-based particles is less than 15%, the secured space is difficult to buffer the volume expansion of nanosilicon due to lithium absorption, and the mechanical strength of the carbonaceous material is difficult to withstand large expansion stress, so the structure of the silicon-based particles collapses and the electrochemical properties deteriorate. If the porosity α1 of the silicon-based particles exceeds 60%, the pores are too large, and the compressive strength of the carbonaceous material decreases, so that the silicon-based particles easily collapse during processing, and the electrochemical properties deteriorate.

[0017] In the present invention, the porosity α2 of the negative electrode piece is 15% to 42%, and for example, the lower limit of the porosity α2 of the negative electrode piece may include 15%, 18%, or 27%, and the upper limit of the porosity α2 of the negative electrode piece may include 30%, 35%, or 42%. If the porosity α2 of the negative electrode piece is less than 15%, the electrolyte is difficult to penetrate sufficiently, the transportation distance of the lithium ions increases, and the kinetics of the lithium ion battery deteriorates. If the porosity α2 of the negative electrode piece is more than 42%, poor contact is likely to occur between the silicon-based particles and the graphite particles during the cycle of the lithium ion battery, which deteriorates the cycle characteristics and reduces the energy density of the lithium ion battery.

[0018] In one embodiment of the present invention, the porosity α1 of the silicon-based particles and the silicon content B in the silicon-based particles satisfy P=0.5α1 / (B-α1B), 0.2≦P≦1.6. For example, the lower limit of the P value may include 0.2, 0.4, 0.5, or 0.8, and the upper limit of the P value may include 1.1, 1.5, or 1.6. If the P value is less than 0.2, the pores secured in the silicon-based particles are difficult to buffer the volume expansion of nanosilicon due to lithium absorption, and the mechanical strength of the carbonaceous material is difficult to withstand large expansion stress, so that the structure of the silicon-based particles collapses and the electrochemical properties deteriorate. If the P value exceeds 1.6, the pores secured in the silicon-based particles are too large, and the mechanical compressive strength of the carbonaceous material deteriorates, so that the silicon-based particles easily collapse during processing, exposing a large amount of fresh interfaces, deteriorating the initial efficiency and cycle characteristics, and reducing the energy density of the lithium-ion battery. Therefore, by controlling the P value within the above range, the energy density, cycle characteristics, and expansion prevention characteristics of the lithium ion battery can be effectively improved.

[0019] Here, the silicon content B in the silicon-based particles is 20wt% to 60wt%. For example, the lower limit of the silicon content B may include 20wt% or 35wt%, and the upper limit of the silicon content B may include 40wt% or 60wt%. If the silicon content B is less than 20wt%, the gram capacity of the negative electrode material layer is small. If the silicon content B is more than 60wt%, the volume change rate during the lithium release process increases, more SEI is generated, and the consumption of lithium ions and electrolyte in the lithium ion battery is accelerated, and the impedance of the lithium ion battery is significantly increased.

[0020] In one embodiment of the present invention, the content of silicon-based particles in the negative electrode material layer is 3wt% to 80wt%. For example, the lower limit of the content of silicon-based particles in the negative electrode material layer may include 3wt%, 10wt%, 20wt%, 25wt%, 30wt%, 35wt%, or 40wt%, and the upper limit of the content of silicon-based particles in the negative electrode material layer may include 45wt%, 55wt%, 60wt%, 70wt%, or 80wt%. By controlling the content of silicon-based particles in the negative electrode material layer within the above range, the gram capacity of the negative electrode material layer is kept high, and the energy density of the lithium ion battery is improved.

[0021] In the present invention, the content of the graphite particles in the negative electrode layer is not particularly limited as long as the object of the present invention can be achieved, and for example, the content of the graphite particles in the negative electrode layer may be 20wt% to 97wt%, the lower limit of the content of the graphite particles in the negative electrode layer may include 20wt%, 25wt%, 30wt%, or 40wt%, and the upper limit of the content of the graphite particles in the negative electrode layer may include 50wt%, 60wt%, 70wt%, 80wt%, or 90wt%. By controlling the content of the graphite particles in the negative electrode layer within the above range, the conductivity of the negative electrode layer is increased, the contact with the electrolyte is reduced, and the generation of SEI is reduced.

[0022] In one embodiment of the present invention, the peak intensity ratio of the D peak to the G peak in the Raman measurement of the silicon-based particle is 0.2 to 2, and the D peak has a shift range of 1255 cm in the Raman spectrum of the silicon-based particle. -1 ~1355cm -1 The G peak has a shift range of 1575 cm in the Raman spectrum of silicon-based particles. -1 ~1600cm -1 When the peak intensity ratio of the D peak and the G peak in the Raman measurement of the silicon-based particles is controlled within the above range, the carbonaceous material of the silicon-based particles has sufficient pore defects, which is advantageous in suppressing the expansion deformation during cycling, and improves the expansion prevention property and cycle property of the negative electrode piece.

[0023] In one embodiment of the present invention, the silicon-based particles have a carbon material on the surface thereof. In the present invention, the type of carbon material is not particularly limited as long as the object of the present invention can be achieved. For example, the carbon material may include at least one of amorphous carbon, carbon nanotubes, carbon nanoparticles, vapor-grown carbon fibers, and graphene. In some embodiments of the present invention, the carbon nanotubes may include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. In the present invention, the method for producing silicon-based particles having a carbon material on the surface thereof is not particularly limited as long as the object of the present invention can be achieved. In the present invention, the content of the carbon material is not particularly limited as long as the object of the present invention can be achieved. For example, the content of the carbon material may be 0.01 wt% to 1 wt% of the silicon-based particles, for example, 0.01 wt%, 0.1 wt%, 0.5 wt%, or 1 wt%. The presence of a carbon material on the surface of the silicon-based particles is advantageous in improving the interfacial stability of the surface of the silicon-based particles, and thus can restrain the movement of the silicon-based particles, effectively buffering the collapse of the structure caused by the volumetric expansion and contraction of the silicon-based particles, and avoiding the generation of a new interface, thereby improving the cycle characteristics and expansion and deformation of the negative electrode pieces.

[0024] In one embodiment of the present invention, the silicon-based particles have a polymeric material on the surface thereof. In the present invention, the type of polymeric material is not particularly limited as long as the object of the present invention can be achieved. For example, the polymeric material may include at least one of polyvinylidene fluoride (PVDF), carboxymethylcellulose (CMC), sodium carboxymethylcellulose (CMC-Na), polyvinylpyrrolidone (PVP), polyacrylic acid, polystyrene butadiene rubber, and derivatives thereof. In some embodiments of the present invention, the polymeric material may include sodium carboxymethylcellulose, polyvinylpyrrolidone, polyvinylidene fluoride, and sodium polyacrylate (PAANa). In the present invention, the method for producing silicon-based particles having a polymeric material on the surface thereof is not particularly limited as long as the object of the present invention can be achieved. In the present invention, the content of the polymeric material is not particularly limited as long as the object of the present invention can be achieved. The ... 0 wt% to 0.4 wt% of the silicon-based particles, and may be, for example, 0 wt%, 0.025 wt%, 0.15 wt%, or 0.4 wt%.

[0025] In one embodiment of the present invention, the average particle diameter Dv50 of the silicon-based particles is less than 20 μm. Without being limited by any theory, if the average particle diameter Dv50 of the silicon-based particles exceeds 20 μm, problems such as scratches are likely to occur during processing of the negative electrode pieces, and at the same time, the contact sites between the particles are reduced, which affects the cycle characteristics of the negative electrode pieces. By controlling the average particle diameter Dv50 of the silicon-based particles of the present invention within the above range, the cycle characteristics of the negative electrode pieces can be improved. In the present invention, the particle diameter of the graphite particles is not particularly limited as long as the object of the present invention can be achieved.

[0026] In one embodiment of the present invention, the silicon-based particles have a specific surface area of ​​50 m 2 Without being limited by any theory, it is assumed that the specific surface area of ​​the silicon-based particles is less than 50 m 2When the specific surface area of ​​the silicon-based particles is larger than 1 / g, the specific surface area of ​​the silicon-based particles is too large, which affects the properties of the lithium ion battery due to side reactions, and at the same time, a higher proportion of the binder is required to be consumed, which reduces the adhesion between the negative electrode material layer and the negative electrode current collector, resulting in a relatively high rate of increase in internal resistance. In the present invention, the specific surface area of ​​the graphite particles is not particularly limited as long as it can achieve the object of the present invention.

[0027] The negative electrode piece of the present invention has a compressed density of 1.0 g / cm 3 ~1.9g / cm 3 This allows the lithium ion battery to have a high energy density.

[0028] In the present invention, the negative electrode current collector contained in the negative electrode piece is not particularly limited as long as the object of the present invention can be achieved, and may include, for example, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collector. In the present invention, the thickness of the negative electrode current collector and the negative electrode material layer is not particularly limited as long as the object of the present invention can be achieved, and for example, the thickness of the negative electrode current collector is 6 μm to 10 μm, and the thickness of the negative electrode material layer is 30 μm to 120 μm. In the present invention, the thickness of the negative electrode piece is not particularly limited as long as the object of the present invention can be achieved, and for example, the thickness of the negative electrode piece is 50 μm to 150 μm.

[0029] The negative electrode piece may further include an optional conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The configuration of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder.

[0030] The positive electrode piece of the present invention is not particularly limited as long as it can achieve the object of the present invention. For example, the positive electrode piece generally includes a positive electrode collector and a positive electrode material layer. The positive electrode collector is not particularly limited as long as it can achieve the object of the present invention, and may include, for example, aluminum foil, aluminum alloy foil, or a composite current collector. The positive electrode material layer includes a positive electrode active material, and the positive electrode active material is not particularly limited as long as it can achieve the object of the present invention, and may include, for example, at least one of nickel cobalt manganese oxide (811, 622, 523, 111), nickel cobalt lithium aluminum oxide, lithium iron phosphate, lithium excess manganese material, lithium cobalt oxide, lithium manganate, lithium manganese iron phosphate, and lithium titanate. In the present invention, the thickness of the positive electrode collector and the positive electrode material layer is not particularly limited as long as it can achieve the object of the present invention. For example, the thickness of the positive electrode collector is 8 μm to 12 μm, and the thickness of the positive electrode material layer is 30 μm to 120 μm.

[0031] The positive electrode piece may further include an optional conductive layer, the conductive layer being located between the positive electrode current collector and the positive electrode material layer. The configuration of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder.

[0032] The conductive agent is not particularly limited as long as it can achieve the object of the present invention. For example, the conductive agent may include at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fiber, flake graphite, Ketjen black, graphene, and the like. The binder is not particularly limited, and any binder known in the art may be used as long as it can achieve the object of the present invention. For example, the binder may include at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyimide, polyamide-imide, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinylidene fluoride, polytetrafluoroethylene (PTFE), carboxymethylcellulose, and sodium carboxymethylcellulose (CMC-Na), and the like. For example, the binder may be selected as styrene-butadiene rubber (SBR).

[0033] The separator of the present invention is not particularly limited as long as it can achieve the object of the present invention. For example, the separator of the present invention may include at least one of polyolefin (PO)-based separators mainly composed of polyethylene (PE) and polypropylene (PP), polyester films (e.g., polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex, and aramid films, woven films, nonwoven films (nonwoven fabrics), microporous films, composite films, separator papers, press films, and spun films.

[0034] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a film, or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic material.

[0035] For example, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are not particularly limited and may include, for example, at least one of alumina, silica, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is not particularly limited and may be, for example, one or a combination of a plurality of materials selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The polymer layer includes a polymer, and the polymer material includes at least one of polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene), etc. The lithium ion battery of the present invention further includes an electrolyte, and the electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte solution, and the electrolyte solution includes a lithium salt and a non-aqueous solvent.

[0036] In some embodiments of the present invention, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. By way of example, the lithium salt may be selected from LiPF6 since it provides high ionic conductivity and can improve cycleability.

[0037] The non-aqueous solvent may be a carbonate compound, a carboxylic acid ester compound, an ether compound, another organic solvent, or a combination thereof. The carbonate compound may be a chain carbonate compound, a cyclic carbonate compound, a fluorocarbonate compound, or a combination thereof. Examples of the chain carbonate compound include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof. Examples of the cyclic carbonate compound include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof. Examples of the fluorocarbonate compound are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof. Examples of the carboxylic acid ester compound are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, mevalonolactone, caprolactone, and combinations thereof. Examples of the ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.Examples of such other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters, and combinations thereof.

[0038] The present invention further provides an electrochemical device comprising the negative electrode piece according to any one of the above embodiments, the electrochemical device having good cycle characteristics, anti-expansion characteristics, rate characteristics and volumetric energy density.

[0039] The electrochemical device of the present invention is not particularly limited and may include any device in which an electrochemical reaction occurs. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0040] The present invention provides an electronic device including an electrochemical device according to the embodiments of the present invention, which has good cycle characteristics, anti-expansion characteristics, rate characteristics, and volumetric energy density.

[0041] The electronic device of the present invention is not particularly limited and may be used as any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a portable facsimile, a portable copy machine, a portable printer, a stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini disc, a walkie-talkie, an electronic notebook, a calculator, a memory card, a portable tape recorder, a radio, a backup power source, a motor, an automobile, a motorcycle, a bicycle assisted bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, a power tool, a flashlight, a camera, a large household storage battery, and a lithium ion capacitor.

[0042] The manufacturing process of the electrochemical device is well known to those skilled in the art and is not particularly limited in the present invention. For example, the electrochemical device may be manufactured by stacking a positive electrode piece and a negative electrode piece with a separator therebetween, wrapping or folding the stack as necessary, placing the stack in a case, injecting an electrolyte into the case, and sealing the case. The separator used here is the separator provided in the present invention. In addition, an overcurrent protection element, a lead plate, etc. may be provided in the case as necessary to prevent an internal pressure rise of the electrochemical device, overcharging and overdischarging, etc.

[0043] The negative electrode piece provided by the present invention, the electrochemical device including the negative electrode piece, and the electronic device include silicon-based particles and graphite particles in the negative electrode material layer of the negative electrode piece, and in the silicon-based particles having a particle diameter of more than 3 μm, the Si content in the surface region is smaller than the Si content in the internal region, thereby reducing the surface stress of the negative electrode piece and improving the interfacial stability between the silicon-based particles and the electrolyte, and effectively improving the cycle characteristics and expansion and deformation problems of the electrochemical device. [Brief description of the drawings]

[0044] In order to more clearly describe the technical solutions of the present invention and the prior art, the following will briefly describe the drawings used in the embodiments and the prior art. It is obvious that the drawings below are only some embodiments of the present invention.

[0045] [Figure 1] FIG. 1 is a cross-sectional view of a silicon-based particle according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a SEM (scanning electron microscope) image of a cross-section of a silicon-based particle according to one embodiment of the present invention. [Diagram 3] Figure 3 is a linear scan image taken by EDS (X-ray energy spectroscopy) at the position indicated by the arrow in Figure 2. [Figure 4] FIG. 4 is an SEM image of a cross section of a negative electrode piece according to one embodiment of the present invention. [Diagram 5] FIG. 5 is an enlarged SEM image of FIG. [Figure 6] FIG. 6 shows cycle decay curves of Example 2 of the present invention and Comparative Example 1. [Figure 7] FIG. 7 shows the expansion curves of the lithium ion batteries of Example 2 of the present invention and Comparative Example 1.

[0046] Legend: 10 pores of silicon-based particles; 20 pores of anode strip; 30 surface region; 40 internal region; 50 particle interface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0047] In order to clearly define the objectives, technical solutions and advantages of the present invention, the present invention will be described in more detail below with reference to the drawings and embodiments. It is clear that the described embodiments are only some embodiments of the present invention, and are not all embodiments. All other technical solutions obtained by those skilled in the art based on the embodiments of the present invention are within the protection scope of the present invention.

[0048] In the embodiment of the present invention, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to a lithium ion battery.

[0049] Fig. 1 is a cross-sectional view of a silicon-based particle according to one embodiment of the present invention. Referring to Fig. 1, in the silicon-based particle, when the mass percentage of Si in a surface region 30 where the distance from the outer surface of the silicon-based particle to the outer surface is less than H is M1, and the mass percentage of Si in an internal region 40 where the distance from the outer surface of the silicon-based particle to the outer surface is more than H is M2, M1 and M2 satisfy M2>M1. In Fig. 1, L is a tangent to the outer surface of the silicon-based particle.

[0050] Fig. 2 is an SEM image of a cross section of a silicon-based particle according to one embodiment of the present invention, and Fig. 3 is an EDS line scan image of a particle interface 50 at the position of the arrow in Fig. 2. Referring to Fig. 3, in the silicon-based particle, the Si content in a region where the distance from the outer surface to the outer surface is less than 0.2 µm is smaller than the Si content in a region where the distance from the outer surface to the outer surface is more than 0.2 µm.

[0051] Fig. 4 is an SEM image of a cross section of a negative electrode piece according to one embodiment of the present invention, and Fig. 5 is an SEM image enlarged from Fig. 4. Referring to Fig. 5, pores 10 in the silicon-based particles are pores inside the silicon-based particles, and pores 20 in the negative electrode piece refer to pores between each particle of the negative electrode material layer.

[0052] Working Example Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples. Various tests and evaluations are performed as described below. In addition, "parts" and "%" are based on mass unless otherwise specified.

[0053] Measurement method and equipment: Determination of silicon content in silicon-based particles: Silicon-based particles were sliced ​​and the average mass percentages of elements were determined by EDS linear scan measurements.

[0054] Measurement of the porosity of the negative electrode strips: Using the same mold, 50 negative electrode pieces with a radius d were cut out, and the thickness h of each electrode piece was measured using a ten-thousandth micrometer. The electrode pieces were then placed in the sample chamber of the AccuPyc1340 instrument, and the true volume V of the electrode piece was measured according to Boyle's law PV=nRT by filling the electrode pieces with helium gas (He) in the sealed sample chamber. After the measurement was completed, the number of small circular pieces was counted, and the apparent volume πd of the sample was calculated. 2 ×50×h was calculated. Finally, the formula α2=1-V / πd 2 × 50 × h to obtain the porosity α2 of the negative electrode piece.

[0055] Measuring the porosity of silicon-based particles: The interface of silicon-based particles was photographed with a scanning transmission electron microscope (STEM), and the porosity was measured using the obtained STEM image. Specifically, the STEM image was binarized using a threshold value using the software Image J, the size was standardized using a proportional scale, and the pore area was statistically analyzed using Analyze Particles to obtain the area ratio occupied by the pores, i.e., the porosity α1 of the silicon-based particles. 20 or more silicon-based particles were randomly selected from the pole piece and measured in the same manner, and the average value was taken.

[0056] Measurement of specific surface area: The amount of gas adsorbed onto the solid surface was measured at each relative pressure at constant temperature and low temperature (-199℃ to -193℃), and then the monolayer adsorption amount of the sample was determined based on the Brunauer-Emmett-Teller adsorption theory and its formula (BET formula), and the specific surface area of ​​the solid was calculated.

[0057] BET Official:

[0058]

number

[0059] W - mass of gas adsorbed by a solid sample under relative pressure (P / P0), in cm 3 / g, Wm - the saturated adsorption amount of gas that covers the entirety of one monolayer, unit cm 3 / g, C---constants related to the heat of adsorption and heat of aggregation of the first layer, Slope: (c-1) / (WmC), Intercept: 1 / WmC, Total specific surface area: (Wm×N×Acs / M), Specific surface area: S = St / m, m: mass of sample, Acs: average area occupied by each N2 molecule 16.2A 2 .

[0060] 1.5 to 3.5 g of powder sample was weighed out and placed in a measurement sample tube of a TriStar II 3020, and the measurement was performed after degassing at 200 °C for 120 min.

[0061] How to measure the gram capacity of the negative electrode layer: The gram capacity of the negative electrode material layer was measured using a button battery. The assembled button battery was left to stand for 5 minutes in a constant temperature environment of 25°C, discharged at 0.05C until it reached 0.005V, left to stand for 5 minutes, and discharged at 20μA until it reached 0.005V. The total discharge capacity of both steps was D0. After leaving to stand for 5 minutes, it was charged at 0.1C until it reached 2.0V. The charge capacity at this time was C0. The initial charge efficiency was C0 / D0×100%.

[0062] Measurement of the compressed density of the negative electrode pieces: Use a punching machine to punch out a piece with area S from the negative electrode, weigh its mass M1, and measure its thickness with a one-tenth micrometer to denote it as H1. Use the same punching machine to punch out a current collector with the same area S, weigh its mass M2, and measure its thickness H2 with a one-tenth micrometer. The compressed density of the negative electrode is (M1-M2) / (H1-H2) / S.

[0063] Particle size measurement: Approximately 0.02 g of powder sample was added to a clean 50 ml beaker, approximately 20 ml of deionized water was added, and a few drops of 1% surfactant were added to completely disperse the powder in water. The powder was then ultrasonicated in an ultrasonic cleaner at 120 W for 5 minutes, and the particle size distribution was measured using a laser scattering particle sizer, MasterSizer2000. Dv50 is the diameter of a particle whose cumulative volume is 50% in a volume-based particle size distribution measured by a laser scattering particle sizer.

[0064] Powder material button cell test method: The negative electrode active material obtained in the examples, conductive carbon black, and binder PAA (modified polyacrylic acid) were added to deionized water in a mass ratio of 80:10:10, stirred to form a slurry, coated with a doctor blade to form a coating layer of 100 μm in thickness, dried in a vacuum dryer at about 85 ° C for 12 hours, and then cut out pieces of 1 cm in diameter with a press in a dry environment. In a glove box, a lithium metal piece was used as a counter electrode, a Ceglard composite membrane was used as a separator, and an electrolyte was poured to assemble a button battery. The charge and discharge measurement of the battery was performed using a LAND series battery tester, and the charge and discharge capacity was measured.

[0065] First, the material was discharged at 0.05C until it reached 0.005V, left to stand for 5 minutes, then discharged at 50μA until it reached 0.005V, left to stand for another 5 minutes, then discharged at 10μA until it reached 0.005V to obtain the initial lithium absorption capacity of the material. Then, the material was charged at 0.1C until it reached 2V to obtain the initial lithium desorption capacity. Finally, the ratio of the initial lithium absorption capacity to the initial lithium desorption capacity was determined as the initial efficiency of the material.

[0066] Measurement of cycle characteristics: The measurement temperature was 25 / 45°C, and the battery was charged at a constant current of 0.7C to 4.4V, charged at a constant voltage of 0.025C, and then left to stand for 5 minutes, after which it was discharged at 0.5C to 3.0V. The capacity obtained in this step was taken as the initial capacity, and measurements were performed in a cycle of 0.7C charge / 0.5C discharge, and the ratio of the capacity of each step to the initial capacity was calculated to obtain a capacity decay curve. The number of cycles at 25°C until the capacity retention rate reached 90% was taken as the room temperature cycle characteristic of the lithium ion battery, and the number of cycles at 45°C until the capacity retention rate reached 80% was taken as the high temperature cycle characteristic of the lithium ion battery, and the cycle characteristics of the material were obtained by comparing the number of cycles.

[0067] Discharge rate measurement: At 25°C, the battery was discharged at 0.2C to 3.0V, allowed to stand for 5 minutes, charged at 0.5C to 4.45V, and then charged at a constant voltage of 0.05C, after which it was allowed to stand for 5 minutes. The discharge rate was adjusted, and discharge measurements were performed at 0.2C, 0.5C, 1C, 1.5C, and 2.0C, respectively, to obtain the respective discharge capacities. The capacities obtained at each rate were then compared with the capacity obtained at 0.2C, and the rate characteristics were compared by comparing the ratio of the capacity at 2C to the capacity at 0.2C.

[0068] Measurement of the swelling rate of a lithium-ion battery when fully charged: A spiral micrometer was used to measure the thickness of a new lithium-ion battery at the initial half-charge state. After repeating this process up to 400 cycles (cls), the lithium-ion battery was in a fully charged state. The spiral micrometer was then used to measure the thickness of the lithium-ion battery at this time, and the thickness was compared with the thickness of a new lithium-ion battery at the initial half-charge state to obtain the full-charge expansion rate of the lithium-ion battery at this time.

[0069] Energy density calculation: After charging the lithium-ion battery to 4.45V at 25℃, the length, width, and height of the lithium-ion battery were measured with a laser thickness gauge to obtain the volume (V) of the lithium-ion battery. The lithium-ion battery was then discharged at 0.2C to 3V to obtain the discharge capacity (C) and average voltage plateau (U) of the lithium-ion battery. The energy density per volume (ED) was then calculated using the formula ED=C×U / V.

[0070] Example 1 <Preparation of negative electrode active material> A porous carbon material with a porosity of 41% was placed in a sealed silicon-containing gas reactor, heated to 500°C, kept at that temperature for 4 hours, cooled, sieved, and demagnetized to obtain silicon-based particles with a porosity α1 of 30%. Here, the carbon content in the silicon-based particles was 60wt%, the silicon content B in the silicon-based particles was 40wt%, the distance was 0.04μm, and the average particle diameter Dv50 of the silicon-based particles was 7.6μm.

[0071] <Preparation of negative electrode piece> The negative electrode active material prepared above, graphite particles, and nano-conductive carbon black were mixed in a mass ratio of 30:66.5:3.5 to obtain a first mixture. The first mixture and binder PAA were added to deionized water in a mass ratio of 95:5 to prepare a slurry with a solid content of 45%, and the mixture was stirred uniformly to obtain a first mixed slurry. The first mixed slurry was uniformly applied to one surface of a copper foil serving as a negative electrode current collector with a thickness of 8 μm, and dried in dry air at 120° C. for 2 minutes, until the weight of the coating layer became 7.5 mg / cm. 2 A negative electrode piece having a negative active material applied on one side was obtained. After the above steps were completed, the coating of one side of the negative electrode plate was completed. Then, the above steps were repeated on the other surface of the negative electrode plate, and a negative electrode plate having a negative active material applied on both sides was obtained. After cold rolling, a negative electrode plate having a porosity α2 of 30% was obtained, and the plate was cut into a size of 1 mm × 61 mm for the next step.

[0072] <Preparation of positive electrode piece> The positive electrode active material lithium cobalt oxide (LiCoO2), nano-conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 97.5:1.0:1.5, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75%, which was then uniformly stirred. The slurry was uniformly applied to one surface of an aluminum foil positive electrode current collector with a thickness of 10 μm, and dried under conditions of 90 ° C to obtain a positive electrode plate coated with a coating layer with a thickness of 110 μm. After the above steps are completed, the coating of one side of the positive electrode plate is completed. After that, the above steps are repeated on the other surface of the positive electrode plate to obtain a positive electrode plate coated with the positive electrode active material on both sides. After the coating is completed, the plate is cut into a size of 38 mm x 58 mm and prepared for the next step.

[0073] <Preparation of electrolyte> In a dry argon gas atmosphere, organic solvents ethylene carbonate (EC), methyl ethyl carbonate, and diethyl carbonate were mixed in a mass ratio of EC:EMC:DEC = 30:50:20 to obtain an organic solution. Lithium hexafluorophosphate, a lithium salt, was dissolved in the organic solvent and mixed uniformly to obtain an electrolyte solution with a lithium salt concentration of 1.15 Mol / L.

[0074] <Preparation of separator> Alumina and polyvinylidene fluoride were mixed in a mass ratio of 90:10 and dissolved in deionized water to form a ceramic slurry with a solid content of 50%.Then, the ceramic slurry was uniformly applied to one surface of a porous substrate (polyethylene, thickness 7 μm, average pore size 0.073 μm, porosity 26%) by microgravure coating method, and after drying treatment, a two-layer structure of a ceramic coating layer and a porous substrate was obtained, and the thickness of the ceramic coating layer was 50 μm.

[0075] Polyvinylidene fluoride (PVDF) and polyacrylate were mixed in a mass ratio of 96:4 and dissolved in deionized water to form a polymer slurry with a solid content of 50%. The polymer slurry was then uniformly applied to both surfaces of the two-layer structure of the ceramic coating layer and the porous substrate by microgravure coating, and after drying, a separator was obtained, with the single-layer coating layer made of the polymer slurry having a thickness of 2 μm.

[0076] <Preparation of lithium-ion batteries> The positive electrode pieces, separator, and negative electrode pieces prepared above were stacked in order and wound up to obtain an electrode assembly, with the separator interposed between the positive electrode pieces and the negative electrode pieces to play the role of isolation. The electrode assembly was placed in an aluminum plastic film exterior, dried, and then poured with an electrolyte, and the lithium ion battery was obtained through processes such as vacuum packaging, standing, formation, degassing, and cutting.

[0077] In Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Example 12, Example 13, Example 14, Example 15, Example 16, Example 17, Example 18, Example 19, Example 20, and Example 21, the preparation steps of <Preparation of negative electrode active material>, <Preparation of negative electrode piece>, <Preparation of positive electrode piece>, <Preparation of electrolyte>, <Preparation of separator>, and <Preparation of lithium ion battery> are all similar to those in Example 1, and the changes in preparation-related parameters are as shown in Table 1.

[0078] [Table 1]

[0079] Example 22 <Preparation of negative electrode active material> 1) A porous carbon material with a porosity of 41% was placed in a sealed silicon-containing gas reactor, heated to 500°C and kept at that temperature for 4 hours, cooled, sieved, and demagnetized to obtain silicon-based particles with a porosity α1 of 30%. Here, the carbon content in the silicon-based particles was 60wt%, and the silicon content B in the silicon-based particles was 40wt%. The distance was 0.08μm, and the average particle diameter Dv50 of the silicon-based particles was 7.6μm.

[0080] 2) The silicon-based particles obtained in step 1) were added to single-walled carbon nanotubes (SCNTs) containing sodium carboxymethylcellulose (CMC-Na) as a dispersant, dispersed for 2 hours until a uniform mixed solution was formed, spray-dried to obtain a powder, which was then crushed and sieved through a 400-mesh sieve to obtain a negative electrode material. Here, the mass percentage of silicon-based particles:SCNT:sodium carboxymethylcellulose was 99.75:0.1:0.15.

[0081] <Preparation of negative electrode piece>, <Preparation of positive electrode piece>, <Preparation of electrolyte>, <Preparation of separator>, and <Preparation of lithium ion battery> were the same as in Example 1.

[0082] In Example 23, Example 24, Example 25, Example 26, Example 27, Example 28, Example 29, Example 30, Example 31, Example 32, Example 33, Example 34, Example 35, Example 36, and Example 37, the preparation steps of <Preparation of negative electrode active material>, <Preparation of negative electrode piece>, <Preparation of positive electrode piece>, <Preparation of electrolyte>, <Preparation of separator>, and <Preparation of lithium ion battery> are all the same as those in Example 22, and the changes in preparation-related parameters are as shown in Table 2.

[0083] [Table 2]

[0084] Note: In Table 2, " / " means that the preparation parameter is not present.

[0085] In Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Comparative Example 7, and Comparative Example 8, the preparation steps of <Preparation of negative electrode active material>, <Preparation of negative electrode pieces>, <Preparation of positive electrode pieces>, <Preparation of electrolyte>, <Preparation of separator>, and <Preparation of lithium ion battery> are all the same as in Example 1, and the changes in preparation-related parameters are as shown in Table 3.

[0086] [Table 3]

[0087] The preparation parameters of Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 are as shown in Table 4.

[0088] [Table 4]

[0089] The measurement results of Examples 1, 2, 3, 4, Comparative Examples 1 and 2 are shown in Table 5.

[0090] [Table 5]

[0091] The preparation parameters of Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Comparative Example 3, and Comparative Example 4 are as shown in Table 6.

[0092] [Table 6]

[0093] The measurement results of Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Comparative Example 3, and Comparative Example 4 are shown in Table 7.

[0094] [Table 7]

[0095] The preparation parameters of Example 12, Example 13, Example 14, Example 15, Example 16, Example 17, Example 18, Example 19, Example 20, Example 21, Comparative Example 5, Comparative Example 6, Comparative Example 7, and Comparative Example 8 are as shown in Table 8.

[0096] [Table 8]

[0097] The measurement results of Example 12, Example 13, Example 14, Example 15, Example 16, Example 17, Example 18, Example 19, Example 20, Example 21, Comparative Example 5, Comparative Example 6, Comparative Example 7, and Comparative Example 8 are shown in Table 9.

[0098] [Table 9]

[0099] The preparation parameters of Example 2, Example 22, Example 23, Example 24, Example 25, Example 26, Example 27, Example 28, Example 29, Example 30, Example 31, Example 32, Example 33, Example 34, Example 35, Example 36, and Example 37 are as shown in Table 10.

[0100] [Table 10]

[0101] The measurement results of Examples 2, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, and 37 are shown in Table 11.

[0102] [Table 11]

[0103] As can be seen from Example 1, Example 2, Example 3, Example 4, and Comparative Example 1 and Comparative Example 2, for silicon-based particles with the same Dv50, the Si content in the surface region is smaller than the Si content in the inner region, so that the cycle characteristics and expansion prevention characteristics of the lithium-ion battery can be significantly improved. However, as the surface region with a low Si content becomes larger, the cycle characteristics, expansion prevention characteristics, and energy density of the lithium-ion battery all deteriorate. This is because, when the silicon content of the carbonaceous material is relatively low, some of the pores are not filled, the specific surface area becomes large, the contact area between the silicon-based particles and the electrolyte increases, a large amount of by-products are generated, the limited lithium ions are consumed, and the capacity decay and expansion increase, and the gram capacity of the negative electrode material layer is further reduced, resulting in a significant decrease in the energy density of the lithium-ion battery. Figure 6 shows the cycle decay curves of Example 2 and Comparative Example 1, and Figure 7 shows the expansion curves of Example 2 and Comparative Example 1.

[0104] As can be seen from Example 5, Example 6, Example 7, Example 8, Example 9, and Comparative Example 3 and Comparative Example 4, when the silicon content B is constant, there is no significant difference in the gram capacity of the negative electrode material layer, and with the increase in the porosity of the silicon-based particles, the specific surface area of ​​the silicon-based particles increases.

[0105] As can be seen from Examples 7, 10, and 11, by changing the silicon content B in the silicon-based particles, the P value changes, which affects the gram capacity of the negative electrode material layer and the specific surface area of ​​the silicon-based particles.

[0106] As can be seen from Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, and Comparative Example 3 and Comparative Example 4, if the P value is too small, the pores secured inside the silicon-based particles are difficult to buffer the volume expansion of nanosilicon due to lithium absorption, and at this time, the mechanical strength of the carbonaceous material is difficult to withstand large expansion stress, so the structure of the silicon-based particles collapses, and the electrochemical properties of the lithium-ion battery are deteriorated. If the P value is too large, the pores secured inside the silicon-based particles are too large, which deteriorates the mechanical compressive strength of the carbonaceous material, and the silicon-based particles are easy to collapse during processing, and a large amount of fresh interface is exposed, which not only deteriorates the initial efficiency and cycle properties of the lithium-ion battery, but also reduces the energy density of the entire lithium-ion battery. If the P value is within the limit range of the present invention, the cycle properties, expansion prevention properties and volumetric energy density of the lithium-ion battery can be effectively improved, and the silicon-based particles at this time can achieve both structural stability and processability while securing a certain space to accommodate the expansion of silicon due to lithium absorption.

[0107] As can be seen from Example 12, Example 13, Example 14, Example 15, Example 16, and Comparative Example 5 and Comparative Example 6, when the porosity of silicon-based particles is constant, if the porosity of the negative electrode piece is too low, the cycle characteristics and expansion characteristics of the lithium ion battery will be significantly deteriorated. This is because the pores inside the silicon-based particles cannot completely buffer the volume expansion of silicon caused by lithium absorption, and it is necessary to rely on the porosity of the negative electrode piece to further buffer the expansion of silicon caused by lithium absorption, and the volume expansion makes it difficult for the electrolyte to penetrate sufficiently, and the transportation distance of lithium ions increases, which deteriorates the dynamics of the lithium ion battery. If the porosity of the negative electrode piece is too high, the gap between the particles of the negative electrode material layer is too large, and the contact area between the particles is reduced, so the insertion position of lithium ions is reduced, and the lithium ion battery is easily peeled off during the cycle, which significantly deteriorates the cycle characteristics, expansion prevention characteristics and dynamics of the lithium ion battery, and the compression density of the negative electrode piece is reduced, and the volume energy density of the lithium ion battery is also significantly reduced.

[0108] As can be seen from Example 17, Example 18, Example 19, Example 20, Example 21, and Comparative Example 7 and Comparative Example 8, when the porosity of the negative electrode piece is constant, if the porosity of the silicon-based particles is too low, the cycle characteristics and expansion characteristics of the lithium-ion battery will be significantly deteriorated.This is because the space secured inside the silicon-based particles is difficult to buffer the volume expansion of nanosilicon caused by lithium absorption, and at this time, the mechanical strength of the carbonaceous material is difficult to withstand large expansion stress, and the structure of the silicon-based particles is easily collapsed during cycling.If the porosity of the silicon-based particles is too high, the compressive strength of the carbonaceous material is reduced, the silicon-based particles are easily collapsed during processing, the electrical characteristics are deteriorated, and the compressed density of the electrode piece is reduced, which leads to a reduction in the volumetric energy density of the lithium-ion battery.

[0109] As can be seen from Examples 12, 13, 14, 15, 16, 17, 18, 19, 20 and 21, by rationally combining the porosity of the negative electrode piece of the lithium ion battery with the porosity of the silicon-based particles, the cycle characteristics and expansion prevention characteristics of the lithium ion battery can be more effectively improved, and the volumetric energy density of the lithium ion battery can be improved.

[0110] As can be seen from the comparison of Example 22, Example 23, Example 24, Example 25, Example 26, Example 27, Example 28, Example 29, Example 30, Example 31, Example 32, Example 33, Example 34, Example 35, Example 36, and Example 37 with Example 2, by adding 0.1 wt% SCNT to the surface of the silicon-based particles, the cycle characteristics can be significantly improved, by adding 0.1 wt% MCNT, the cycle characteristics can be slightly improved, and by adding 0.05 wt% SCNT and 0.05 wt% MCNT, the cycle characteristics can be improved to some extent. In Examples 22, 25, 26, 27, and 28, the amount of SCNT added was changed and the amount of SCNT added was controlled to be ≦0.5%, but when the amount of SCNT added reached 0.5 wt%, the improvement in the cycle characteristics was not clear compared to the amount of 0.1 wt%, and the initial efficiency was deteriorated on the contrary. When the amount of SCNT added reached 1 wt%, the slurry became unworkable due to too much SCNT. In Example 22, Example 29, Example 30, and Example 31, different dispersants were compared. When no dispersant was added, the dispersion effect of SCNT was low, and the cycle characteristics and deformation of the lithium-ion battery were deteriorated. When PVP and PVDF were used as dispersants, the cycle characteristics were slightly deteriorated compared to the cases of CMC-Na and PAANa. In Examples 22, 32, 33, and 34, the amount of dispersant added was changed. When the amount of dispersant was 0.4 wt%, the dispersion effect was improved, but if the amount of dispersant was too much, the rate characteristics were deteriorated. When the amount of dispersant was 0.025 wt%, the dispersion effect was low, and the cycle characteristics and rate characteristics were deteriorated compared to the case where the dispersant content was 0.15 wt%. In Examples 32, 35, 36, and 37, different carbon material coatings were compared. The results show that the coating effect of CNTs and graphene is the best, because the coating of CNTs and graphene not only improves the electronic conductivity of the material, but also increases the contact points between the materials and reduces the cycle decay caused by poor contact.

[0111] From the above analysis, the negative electrode piece provided by the present invention has a silicon-based particle having a particle diameter of more than 3 μm, and the Si content in the surface region is lower than the Si content in the internal region, thereby reducing the surface stress of the negative electrode piece, improving the interfacial stability between the silicon-based particle and the electrolyte, and significantly improving the cycle characteristics and expansion and deformation problems of the electrochemical device.

[0112] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention are included in the scope of protection of the present invention.

Claims

1. A negative electrode piece, a negative electrode material layer, the negative electrode material layer including silicon-based particles and graphite particles, the silicon-based particles including silicon and carbon; The silicon-based particles include silicon-based particles having a particle diameter of more than 3 μm and a Si content in a surface region that is smaller than a Si content in an inner region, The surface region refers to a region from the outer surface of the silicon-based particle to the outer surface at a distance of 0.04 μm or more and less than 0.2 μm, and the internal region refers to a region from the outer surface of the silicon-based particle to the outer surface at a distance of more than 0.2 μm, The porosity α of the silicon-based particles 1 is 15% to 60%, and the porosity α 2 is 15% to 42%, the negative electrode piece.

2. The porosity α of the silicon-based particles 1 and the porosity α of the negative electrode piece 2 The negative electrode piece according to claim 1 , wherein the sum α of and satisfies 40%<α<90%.

3. The porosity α of the silicon-based particles 1 and the silicon content B in the silicon-based particles is P=0.5α 1 / (B-α 1 B) 0.2≦P≦1.6 is satisfied; The negative electrode piece according to claim 2 , wherein the silicon content B in the silicon-based particles is 20 wt % to 60 wt %.

4. The negative electrode piece according to claim 1 , wherein the content of silicon-based particles in the negative electrode material layer is 3 wt % to 80 wt %.

5. The silicon-based particles have a peak intensity ratio of a D peak to a G peak in a Raman measurement of 0.2 to 2; The D peak has a shift range of 1255 cm in the Raman spectrum of silicon-based particles. -1 ~1355cm -1 The G peak has a shift range of 1575 cm in the Raman spectrum of silicon-based particles. -1 ~1600cm -1 2. The negative electrode piece of claim 1, wherein the peak is

6. 2. The anode piece of claim 1, wherein the silicon-based particles have a carbon material present on the surface thereof, the carbon material including at least one of amorphous carbon, carbon nanotubes, carbon nanoparticles, vapor-grown carbon fibers, and graphene.

7. The negative electrode piece according to claim 1 , wherein the silicon-based particles have an average particle diameter Dv50 of less than 20 μm.

8. The specific surface area of ​​the silicon particles is 50 m 2 2. The negative electrode piece of claim 1, wherein the anode piece has a surface area of ​​less than 1 / g.

9. An electrochemical device comprising the negative electrode piece according to any one of claims 1 to 8.

10. An electronic device comprising the electrochemical device of claim 9.

Citation Information

Patent Citations

  • Negative electrode material, nonaqueous electrolyte secondary battery, and method for manufacturing negative electrode material

    JP2011198614A

  • Negative electrode material for lithium secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2012043547A

  • Negative electrode active material for nonaqueous electrolyte secondary batteries

    WO2013172378A1